2007
DOI: 10.1063/1.2789183
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz emission from vertically aligned InN nanorod arrays

Abstract: Terahertz emission from indium nitride (InN) nanorods and InN film grown by molecular-beam epitaxy on Si(111) substrates has been investigated. Terahertz emission from InN nanorods is at least three times more intense than that from InN film and depends strongly on the size distribution of the nanorods. Surface electron accumulation at the InN nanorods effectively screens out the photo-Dember field in the accumulation layer formed under the surface. The nanorods with considerably large diameter than the thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 12 publications
(4 reference statements)
1
40
1
Order By: Relevance
“…The experimental details can be found elsewhere. 9 It is known that photocarriers generated close to the surfaces of semiconductors can be accelerated by an appropriate electric field and the resultant transient electric dipole can lead to the generation of terahertz pulses. The electric field can be provided either externally by separated electrodes in photoconductive antennas or internally by the photo-Dember field or by the surface depletion/accumulation field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental details can be found elsewhere. 9 It is known that photocarriers generated close to the surfaces of semiconductors can be accelerated by an appropriate electric field and the resultant transient electric dipole can lead to the generation of terahertz pulses. The electric field can be provided either externally by separated electrodes in photoconductive antennas or internally by the photo-Dember field or by the surface depletion/accumulation field.…”
mentioning
confidence: 99%
“…Due to its extremely low probability of intervalley scattering and strong intrinsic electric field, InN has received much attention in terahertz range applications. [5][6][7][8][9][10][11] Typically, as-grown InN film is unintentionally doped n-type and terahertz emission from the undoped InN is much weaker than that from InAs due to large screening from high intrinsic carrier density. Doping InN with proper acceptors, such as Mg, is expected to reduce the carrier density and enhance the radiation intensity.…”
mentioning
confidence: 99%
“…In recent literature, it has been shown that the THz emission efficiency can be substantially increased if the bulk semiconductor is replaced with a structured surface. For example, emission from porous InP, 4 InN nanorods, 5 and ZnSe nanograins 6 has been reported as two orders of magnitude larger than their corresponding bulk samples. Likewise, silicon nanowires 7 and black silicon 8 have demonstrated much stronger emission than bare silicon wafers.…”
mentioning
confidence: 99%
“…In recent literature, it has been shown that the THz emission efficiency can be substantially increased if the bulk semiconductor is replaced with a structured surface. For example, emission from porous InP, 4 InN nanorods, 5 and ZnSe nanograins 6 has been reported as two orders of magnitude larger than their corresponding bulk samples. Likewise, silicon nanowires 7 and black silicon 8 have demonstrated much stronger emission than bare silicon wafers.…”
mentioning
confidence: 99%